Pragmalinguistic aspects of compound nouns in English and Uzbek - Yuldasheva, Nargiza Ergashbayevna; Yusupova, Sanobar Tursunboyevna; Bakhtiyarov, Mukhtorjon Yakubovich; Abdujabborova, Malika Abduvaitovna; Abdurashidova, Nilufar Abdurashidovna (Linguistics and Culture Review, 2021)
This article describes compound nouns in English and Uzbek, their specific pragmatic aspects. Although the problem of compound nouns in linguistics has been studied by many linguists, there are many unsolved problems in comparing compound words in languages ??and analyzing them from a pragmalinguistic point of view. The compound word, which has a special place in the richness of language vocabulary, is in fact a convenient way of naming in simple terms the concepts of events that take place in reality, of existing objects. Hence, it can be concluded that the study of semantic, grammatical and syntactic features of language alone is not enough. As a result, the field of "pragmatics" has found its place in linguistics, having its own goals and objectives. In addition, the article also uses analysis from examples from the literature to reveal the pragmatic nature of compound words. However, scientific examples have shown that no sign is a leading factor in determining the nature of compound words.